New Knowledge from Research – Can Global Congenital Cardiac Surgery Play a Part? A Call for International Collaboration - Jeevan Francis, Jeevan; George, Joseph; Stoica, Serban (Journal of Humanitarian Cardiovascular Medicine, 2022)
Over 1.3 million babies are born each year with congenital heart defects (CHD), with the highest incidence in low-income countries (LIC) and low-middle income countries (LMICs) (Fanaroff., 2012). The Lancet Commission on Global Surgery found that surgically treatable conditions make up 28-32% of the total global burden of diseases, of which most are cardiovascular diseases (Meara et al., 2015). Currently, high-income countries (HICs) undertake mission trips to LICs and LMICs to provide surgical care for those who otherwise would not have access. These trips also provide an opportunity to train the local surgical teams. It has been proposed that there should be a shift in thinking from ‘humanitarian surgery’ to ‘global surgery’, as this benefits both the provider and the receiver. With this change, we should address several limitations in our current infrastructure, including but not limited to, the lack of international research collaboration, the need for globalising and scaling up the paediatric cardiac surgical workforce, offsetting greenhouse gas emissions from mission trips, and opportunities for mentorship and training in LICs.